Comparative effect of protein dosage on nitrogen balance and health outcomes in critically ill patients - Zainab Bibi; Mahpara Safdar; Aiman Hadayat (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the impact of two different doses of proteins on nitrogen balance and clinical outcomes in critically ill patients. Method: The randomised clinical trial was conducted from November 2020 to May 2021 at the intensive care unit of Shifa International Hospital, Islamabad, Pakistan, and comprised critically ill adult patients of either gender at nutritional risk. They were divided into Group I receiving 1g per kilogramme body weight of protein, and Group II receiving 2g per kilogramme body weight of protein. Sequential Organ Failure Assessment scores were calculated for each case. Data was analysed using SPSS 23. Results: Of the 88 patients, 45(51.13%) were in Group I; 28(62.2%) males and 17(37.8%) females with mean age 61±3.5 years. There were 43(48.86%) patients in Group II; 30(69.8%) males and 13(30.2%) females with mean age 64.4±11.6 years (p>0.05). There was no significant difference in nitrogen balance between the groups on day 1 (p=0.381). However, by the discharge day, nitrogen balance was significantly improved in Group II compared to Group I (p=0.001). There was a statistically weak negative relationship between nitrogen balance and Sequential Organ Failure Assessment score (r=-0.131). Nitrogen balance had no significant relationship with the number of ventilated days (r=-0.002), intensive care unit days (r=0.043) and length of hospital stay (r=0.089). Conclusion: Nitrogen balance was significantly better in the critically ill patients who received 2g protein per kilogramme body weight compared to those receiving 1g protein per kilogramme body weight. Clinical Trial Registration: ClinicalTrials.gov, NCT04468503. Key Words: Critically ill patients, Nitrogen balance, Protein prescription, Clinical outcomes.